Газифікація полідисперсних систем кам'яновугільного походження - Білець, Дар'я Юріївна (Національна металургійна академія України, 2020)
Дисертація на здобуття наукового ступеня кандидата технічних наук (доктора філософії) зі спеціальності 05.17.07 – хімічна технологія палива та паливно–мастильних матеріалів (161 – Хімічні технології та інженерія) – Національний технічний університет «Харківський політехнічний інститут», спеціалізована вчена рада Д 08.084.05 при Національній металургійній академії України, Дніпро, 2020. Вперше досліджено вплив складу полідисперсних систем на їх поведінку при підготовці до газифікації: час висипання, кут природного укосу та насипну густину при випусканні з бункеру, а також залипання при змішуванні. Розроблені математичні та графічні залежності впливу витрати повітря від 0,0005 до 0,004 м3/хв та температури 400 до 500 °С на значення констант швидкості та енергії активації, виходу твердого залишку, сконденсованих та газоподібних продуктів при газифікації полідисперсних систем. Розроблено принципову технологічну схеми газифікації полідисперсних систем кам’яновугільного походження, яка може бути рекомендована до впровадження. Основними елементами технологічної схеми є масозмішувач, піч та електроконвертор. Встановлено, що з точки зору витрати електроенергії, оптимальний розмір вуглецевої насадки для електроконвертору становить 10–13 мм та визначено, що витрата вуглецевої насадки (коксу) в процесі газифікації становить 0,014 % від загальної маси наважки, або 0,575 % від маси конвертованої сировини. Встановлено, що при використанні пропонованого способу газифікації полідисперсних систем кам’яновугільного походження можна отримати газ, теплота згоряння якого в 1,62–2,47 рази вища за теплоту згоряння газу, отриманого від газифікації за методом Lurgi. Основні теоретичні положення та експериментальні дані дисертації використовуються в навчальному процесі на кафедрах «Хімічної технології переробки нафти і газу» Національного університету «Львівська політехніка», «Металургійного палива та вогнетривів» Національної металургійної академії України та «Технології переробки нафти, газу та твердого палива» Національного технічного університету «Харківський політехнічний інститут».

The dissertation is devoted to solving an important scientific and practical problem: the development of technology for producing artificial combustible gases by gasification of coke by-products whose properties (high viscosity, adhesion, fluidity, non-crucibility) currently make it impossible to process them. The introduction provides a general description of the work on the topic of the dissertation: the relevance of the topic, substantiated the purpose and main objectives of the work, identified the object, subject and methods of research, shows the scientific novelty and practical value of the data and their approbation. In the first chapter it is provided an overview of Ukrainian and foreign research on methods of application and processing of by-products formed during coke production. The analysis of scientific works on gasification of such materials as one of the main directions of processing of by-products was carried out. In the second chapter it is considered the physical and chemical properties of the main object of study in the direction of the dissertation of heavy coal tars. The expediency of using walnut shells and lignite as a filler, the physical and chemical properties of which are also given in this chapter, is substantiated. A set of standardized methods for the study of selected objects is defined, the characteristics of the necessary equipment for solving the tasks set. In the third chapter it is presented research to determine the optimal ratio of coke by-products and filler in the preparation of polydisperse systems for gasification. It is established that during mixing there is a significant change in the particle size distribution of the studied mixtures. First, the increase in the content of heavy coal tars in the mixtures leads to an increase in the average diameter of the particles, ie their agglomeration occurs. Secondly, the walnut shell is more resistant to mechanical impact compared to lignite. In the fourth chapter it was investigated that kinetic characteristics of the gasification process and the factors influencing them (temperature, air flow, nature of raw materials). It is established that the kinetic curves of the process of joint gasification of polydisperse systems in the temperature range from 400 to 500 ° С and oxidant (air) flow rate from 0.0005 to 0.004 m3/min pass through 3 main stages. The material balances of the investigated materials during іt gasification were determined, namely: yield of solid residue, gaseous and condensed products. The component composition of condensed products for each investigated material and the influence of air flow and temperature on the yield of such components as: Н₂, О₂, N₂, СН₄, СО, СО₂, С₂Н₄ and С₂Н₆. In the fifth chapter the basic technological scheme of gasification of polydisperse systems was developed. The calculation of layer gasification of the studied raw materials by Lurgi technology was performed. The obtained values were compared with the experimental ones. It is established that according to the proposed processing technology, the content of target components of the generator gas, such as CO and H2, is much higher than with classical gasification. The economic estimation of work is defined.
Gasification of polydisperse systems of coal origin
Keywords: автореферат дисертації; полідисперсна система; кам'яновугільні фуси; буре вугілля; шкаралупа волоського горіха; газифікація; електроконверсія; генераторний газ; polydisperse system; heavy coal tars; lignite; walnut shell; gasification; electrical conversion; producer gas; 66.092–977